Lactobacillus plantarum strains show diversity in biofilm formation under flow conditions - P. Rashtchi; M. Tempelaars; E. van der Linden; T. Abee; M. Habibi (Heliyon, 2022)
In many natural and technological applications, microbial biofilms grow under fluid flow. In this project, we investigated the influence of flow on the formation and growth of biofilms produced by gram-positive Lactobacillus plantarum strains WCFS1 and CIP104448. We used an in-house designed device based on a 48-well plate with culture volumes of 0.8 ml, and quantified total biofilm formation under static and flow conditions with flow rates 0.8, 1.6, 3.2 and 4.8 ml/h (with 1, 2, 4 and 6 volume changes per hour) using crystal violet (CV) staining, and determined the number of viable biofilm cells based on plate counts. The amount of total biofilm under flow conditions increased in the CIP 104448 strain, with significantly increased staining at the wall of the wells. However, in the WCFS1 strain, no significant difference in the amount of biofilm formed under flow and static conditions was observed. Plate counts showed that flow caused an increase in the number of viable biofilm cells for both strains. In addition, using enzyme treatment experiments, we found that for WCFS1 in the static condition, the amount of mature biofilm was declined after DNase I and Proteinase K treatment, while for flow conditions, the decline was only observed for DNase I treatment. The CIP104448 biofilms formed under both static and flow conditions only showed a decline in the CV staining after adding Proteinase K, indicating different contributions of extracellular DNA (eDNA) and proteinaceous matrix components to biofilm formation in the tested strains.